FENOMENA SOSIAL BUDAYA DALAM KAJIAN TIGA CERITA RAKYAT KALIMANTAN SELATAN (SOCIO-CULTURAL PHENOMENA IN THE STUDY OF THREE FOLK STORIES SOUTH KALIMANTAN) - Kalsum, Ummi; Rafiek, Muhammad; Cahaya, Noor (Universitas Lambung Mangkurat, 2024)
AbstractSocio-Cultural Phenomena in The Study of Three Folk Stories South Kalimantan. Folklore in South Kalimantan is a form of literature that is passed down from generation to generation by word of mouth. This research aims to describe the socio-cultural reality of South Kalimantan folklore with a sociological study of three folktales, namely: Rajang Waki in Batu Tunggal, Asal Mula Tajau Pecah and Beramban, and Andaru. The research method used is descriptive qualitative. The findings reveal that the folk tales packaged in books published by the South Kalimantan Provincial Language Center, Banjarbaru are entitled, Rajang Waki in Batu Tunggal, The Origin of Tajau Pecah and Beramban, and Andaru, each of which has a storyline depicted in each the title of the folk tale. The folklore of Rajang Waki in Batu Tunggal, a social and cultural phenomenon is summarized in the name Rajang Waki in Batu Tunggal. The second folk tale of the origin of Tajau Pecah and Beramban, the social phenomenon lies in the brothers who took part in a competition and the characters who stand out. The cultural phenomenon is related to the origin of the name